Konsep Penginjeksian Mata Kuliah Baru Pada Program Studi Pendidikan Teknik Elektro - Nadia Utari; Riki Mukhaiyar (invotek, 2020)
Higher education must adapt to the advencement of Science and Technology, one of the ways that Universities can do by implementing curriculum enhancement. Curriculum enhancement can be done by adding new courses. Subjects that are in line with current developments are Image Processing courses. Image Processing is a course in Electrical Engineering that discusses data processing and analyzing data in the form of images to be used as important information as referred. The usage of Image Processing courses is found in daily life, for example on smartphones, parking systems, medical, television and many others that utilize image processing subjects. The characteristics of this study compare two different groups, namely comparing the curriculum of the University of LPTK (Lembaga Pendidikan Tenaga Kependidikan) and the curriculum of the University of Non-LPTK to look for curriculum characteristics in covering different subjects with the characteristics of vocational education, but in accordance with the characteristics of vocational education in considering eye input lectures that are aligned with digital characteristics in the field of vocational education studies. The suitability of the characteristics of the Image Processing course with the characteristics of the LPTK curriculum results in a Semester Learning Plan for Image Processing courses to be applied to the Electrical Engineering Vocational Education study program at State University Of Padang.